Differential effects of inhibitory G protein isoforms on G protein-gated inwardly rectifying K + currents in adult murine atria - Nobles, Muriel (2018)
G protein-gated inwardly rectifying K+ (GIRK) channels are the major inwardly rectifying K+ currents in cardiac atrial myocytes and an important determinant of atrial electrophysiology. Inhibitory G protein α-subunits can both mediate activation via acetylcholine but can also suppress basal currents in the absence of agonist. We studied this phenomenon using whole cell patch clamping in murine atria from mice with global genetic deletion of Gαi2, combined deletion of Gαi1/Gαi3, and littermate controls. We found that mice with deletion of Gαi2 had increased basal and agonist-activated currents, particularly in the right atria while in contrast those with Gαi1/Gαi3 deletion had reduced currents. Mice with global genetic deletion of Gαi2 had decreased action potential duration. Tissue preparations of the left atria studied with a multielectrode array from Gαi2 knockout mice showed a shorter effective refractory period, with no change in conduction velocity, than littermate controls. Transcriptional studies revealed increased expression of GIRK channel subunit genes in Gαi2 knockout mice. Thus different G protein isoforms have differential effects on GIRK channel behavior and paradoxically Gαi2 act to increase basal and agonist-activated GIRK currents. Deletion of Gαi2 is potentially proarrhythmic in the atria.